Retinal neurodegeneration, neuroretinal rim analysis and choroid thickness in pseudoexfoliation syndrome with spectral domain optical coherence tomography - Ana Faria Pereira; Pedro Mota Moreira; Inês Coelho-Costa; Rita Teixeira-Martins; Sérgio Estrela Silva; Cláudia Oliveira-Ferreira (Scientific Reports)
Abstract Pseudoexfoliation (PEX) syndrome is a systemic disorder characterized by the accumulation of fibrillar material in ocular and extraocular tissues, primarily affecting the eye’s anterior segment. While PEX is a known risk factor for open-angle glaucoma, its impact on retinal structures is less understood. This study aims to evaluate macular, circumpapillary retinal nerve fiber layer (cRNFL), and choroidal thickness in PEX patients without glaucoma. This cross-sectional study involved two groups: PEX group and a control group, both without glaucoma damage and with intraocular pressure (IOP) below 19 mmHg. Participants underwent full ophthalmic evaluations. Spectral-domain optical coherence tomography (SD-OCT) was used to measure cRNFL, macular, Bruch’s membrane opening-minimum rim width (BMO-MRW), and choroidal thickness. A total of 60 eyes were included: 38 with PEX and 22 controls. Demographic and clinical characteristics were similar across groups. PEX group had a thinner nasal-inferior cRNFL compared to the control group (p < 0.05). Furthermore, PEX group exhibited significantly reduced thickness in superior, inferior, nasal-inferior, nasal-superior, and total ganglion cell layer (GCL), as well as in nasal-inferior, nasal-superior, and total inner plexiform layer (IPL) compared to the control group (p < 0.05). BMO-MRW thickness tended to be thinner across all sectors in PEX group, although no significant differences were found (p > 0.05). Regarding choroidal thickness, the temporal site was significantly thicker in PEX group (p < 0.05). This study highlights a significant association between PEX syndrome and the thickness reduction of the GCL and IPL, suggesting that these retinal changes could serve as early indicators of glaucoma or reflect broader neurodegenerative processes. Findings also reveal reduced cRNFL thickness in PEX eyes, further supporting the potential for early glaucomatous damage detection. These findings underscore the need for long-term studies to explore PEX-related neurodegeneration and its possible links to broader neurological conditions.